Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Annual Report 2018-2019 / Rapport annuel 2018-2019 - Youth Employment Services (YES) (2019)
Keywords: Official Language Minority Community (OLMC)